2011
DOI: 10.1016/j.ncl.2010.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Movement Disorders Induced by Antipsychotic Drugs: Implications of the CATIE Schizophrenia Trial

Abstract: Synopsis Drug-induced movement disorders have dramatically declined with the widespread use of second generation antipsychotics but remain important in clinical practice and for understanding antipsychotic pharmacology. The diagnosis and management of dystonia, parkinsonism, akathisia, catatonia, neuroleptic malignant syndrome and tardive dyskinesia are reviewed in relation to the decreased liability of the second generation antipsychotics contrasted with evidence from the Clinical Antipsychotic Trials of Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
131
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(144 citation statements)
references
References 102 publications
5
131
0
8
Order By: Relevance
“…While the few randomized controlled trials on treating parkinsonism in patients without SMI had small to moderate effect sizes, [28][29][30] the association between antipsychotic type and dose and parkinsonism symptoms in patients with SMI has also been inconsistent. 7,10 Possible reasons for this are that patients with SMI generally receive such a high dose of antipsychotic medication, 1,30,31 around 2 DDD in our study, that a small dose reduction will have little effect. It is also possible that bradykinesia and parkinsonism symptoms in patients with SMI are not side effects of antipsychotic medication but neurologic soft signs that are part of the endophenotype of the underlying mental disorder.…”
Section: 13mentioning
confidence: 86%
See 1 more Smart Citation
“…While the few randomized controlled trials on treating parkinsonism in patients without SMI had small to moderate effect sizes, [28][29][30] the association between antipsychotic type and dose and parkinsonism symptoms in patients with SMI has also been inconsistent. 7,10 Possible reasons for this are that patients with SMI generally receive such a high dose of antipsychotic medication, 1,30,31 around 2 DDD in our study, that a small dose reduction will have little effect. It is also possible that bradykinesia and parkinsonism symptoms in patients with SMI are not side effects of antipsychotic medication but neurologic soft signs that are part of the endophenotype of the underlying mental disorder.…”
Section: 13mentioning
confidence: 86%
“…[5][6][7][8] The 2 most prevalent movement disorders in this sample are parkinsonism and tardive dyskinesia (TD). 1,9,10 Current treatment guidelines vary for the management of tardive dyskinesia. [11][12][13] For parkinsonism, lowering antipsychotic dose is the recommended first step, followed by switching to a lower dopamine 2 (D 2 ) affinity antipsychotic or an SGA.…”
mentioning
confidence: 99%
“…Furthermore, the pathophysiology behind drug induced acute dystonia also remains unclear [13,14]. It has been suggested that there may be a correlation between D2 receptors and the occurrence of dystonia.…”
Section: Discussionmentioning
confidence: 99%
“…Die am häufigsten beschriebene Substanz, die ein MNS auslösen kann, ist Haloperidol [21,26], was sicherlich auch auf den häufi-gen und hochdosierten Einsatz insbesondere in den frühen Jahren des Gebrauchs von Antipsychotika zurückzuführen ist. Das MNS kann allerdings auch durch die neueren, sogenannten atypischen Antipsychotika oder durch die Reduktion bzw.…”
unclassified